Metacognitive Awareness of Reading Strategies and IELTS Academic Reading Comprehension: A Study of Indonesian and International University Students in Indonesia - Azki Izzur Rabbani; Bambang Yudi Cahyono (English Department - University of Sultan Ageng Tirtayasa, 2026)
This study examines the metacognitive awareness of reading strategies among Indonesian and international university students in Indonesia and its relationship with IELTS Academic Reading comprehension. Employing a quantitative correlational design, the study involved 41 university students (26 Indonesian and 15 international students). Data were collected using the Metacognitive Awareness of Reading Strategies Inventory–Revised (MARSI-R) and participants’ IELTS Academic Reading scores. Descriptive statistics were used to identify levels of metacognitive strategy awareness, while Pearson correlation and multiple linear regression analyses were conducted to examine the relationship between strategy awareness and reading performance. The findings indicate that most participants demonstrated a high level of metacognitive awareness. However, the results reveal no statistically significant relationship between metacognitive awareness and IELTS Academic Reading scores. Therefore, multiple regression analysis further confirmed that metacognitive awareness was not a significant predictor of reading performance. These findings suggest that metacognitive awareness alone may not adequately explain reading outcomes in high-stakes standardized tests such as IELTS. Further research may consider conducting a replication study while adding a larger sample size for better generalization and integrating qualitative findings to enrich the study.